Pengaruh Kompetensi, Independensi dan Pengalaman Kerja Terhadap Kualitas Audit (Studi Empiris Pada Auditor di Kap Wilayah Surakarta dan DIY) - Pradana, R. M Gumelar Aditya, Drs. Wahyono, M.A., Akt., CA (2016)
This study aims to analyze empirically the effect of competence, independence and work experience on audit quality to the auditors working on a public accounting firm in Surakarta and DIY. The population in this study were all auditors working in the public accounting firm in Surakarta and DIY. Sampling was done by using purposive sampling method and obtained a sample of 68 respondents. Primary data collection method used is the questionnaire. Data were analyzed using multiple regression analysis techniques. The results showed that the effect on the competence and independence of audit quality , while work experience had no effect on audit quality . The coefficient of determination shows that jointly competence , independence and work experience to give effect to the dependent variable ( quality audit) amounted to 90.5 % while the remaining 9.5 % is influenced by other factors outside of observation.